The Effect of Weaning Tecnique to Survival Rate and Height Growth of Nyamplung (Calophyllum inophyllum) Plant - Ady Suryawan; Arif Irawan (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2017)
Technical rehabilitation planning of BPDAS Tondano on coastal area has reached 10,000 hectares, thus require many seedlings. Nyamplung has potential as rehabilitation plant in coastal at the same time it can support national demand of biofuel. However the nurseries of nyamplung in North Sulawesi are not optimal and need appropriate information of weaning method. This research used completely randomized design with three treatment factors, namely 1) Cutting the leaves consist of two levels ie D1 (pair leaves) and D2 (intact leaf); 2) Cutting intact seeds, consists of two levels i.e B1 (removed seed) and B2 (intact seeds); and 3) Cutting the roots lenght consist of three levels i.e A1 (5 cm), A2 (10 cm) and A3 (15 cm). There were 180 seedlings taken from seed that germinated using cocopeat media. Results of variance analysis showed that the applied treatment only affect the heigth growth. The survival rate is not affected by all treatments or in the other words survival rate reached 100 %. The treatments on leaves and seeds gave significant effect, on the contrary with root treatment. The treatment of intact leaf (D2) and intact seeds (B2) produced the best height growth responses i.e 4.60 cm and 4.63 cm. Keywords: Calophyllum inophyllum, survival rate, weaning technique, height